Root morphological traits related to phosphorus‐uptake efficiency of soybean, sunflower, and maize. Issue 5 (20th August 2015) - Fernandez, Mariana Cecilia; Rubio, Gerardo
Abstract Many of the plant acquisition strategies for immobile nutrients, such as phosphorus (P), are related to the maximization of soil exploration at minimum metabolic cost. Previous studies have suggested that soybean (Glycine max L.), sunflower (Helianthus annuus L.), and maize (Zea mays L.) differ in their P uptake efficiency. In this investigation we employed these three species to evaluate: (1) the effect of suboptimal P conditions on root morphological traits related to root porosity and fineness and (2) how these traits are related to P‐uptake efficiency. Opaque 25‐L plastic containers were used to grow plants hydroponically. The three species were compared under two P availability levels (low P and high P). Most of the observed responses were in the direction to favor P uptake under low‐P conditions. Compared to P‐sufficient plants, P‐stressed plants of the three species showed higher root‐to‐shoot ratio, specific root length, root porosity and root aerenchyma, and a lower root density. For example, P‐stress increased root porosity by a factor of 2.0, 1.4, and 1.4 in soybean, sunflower, and maize, respectively. Soybean and sunflower were the species with the highest P‐uptake efficiency, expressed as P uptake either per unit root biomass or length. The results demonstrate the central role of aerenchyma development in modifying root length per unit root biomass and, thus, reducing the root's foraging costs. Consequently, aerenchyma is suggested to be a possible mechanism for better P‐uptake efficiency.